Serum and urinary concentrations of arsenic, beryllium, cadmium and lead after an aerobic training period of six months in aerobic athletes and sedentary people - Diego Muñoz; Francisco J. Grijota; Ignacio Bartolomé; Jesús Siquier-Coll; Víctor Toro-Román; Marcos Maynar (Taylor & Francis Group, 2020)
Aim The aim of the present study was to evaluate the possible effect of a period of 6 months of aerobic physical training on serum and urinary concentrations of arsenic (As), beryllium (Be), cadmium (Cd) and lead (Pb), potentially toxic minerals. Methods Twenty-four well-trained, long distance runners (AG), were recruited at the start of their training period. They had been performing training regularly for the previous 2 years, recording an average volume of 120 km per week of rigorous aerobic exercise aimed at high-level competitions (1500 and 5000 m race modalities). Twenty-six untrained, sedentary participants constituted the control group (CG). All participants had been living in the same geographic area for at least 2 years before the start of the survey. Serum and urine samples were obtained from each participant at the beginning and at the end of the 6 months of the training program. The values of each mineral were determined by inductively coupled plasma mass spectrometry (ICP-MS). Additionally, the daily intake of each mineral was evaluated at both moments in time. Results The daily concentrations of trace elements in the diet were similar at the start and the end of the training period without differences between groups. In serum, significant differences between groups were observed in As, Cd and Pb (p < 0.05). Attending to time effects, a significant difference was obtained in Pb (p < 0.05). In urine, significant differences between groups were obtained in all minerals (p < 0.05). According to training period, significant differences were observed in As, Be and Pb (p < 0.05). Finally, the group x time interaction revealed significant differences in As and Be (p < 0.05). Conclusions Aerobic training may constitute a possibly effective method for increasing the elimination of Cd and Pb potentially toxic minerals from the body, especially among highly trained individuals.